Influence of photodynamic therapy combined with antimicrobial peptides on oral biofilm and 3D reconstructed human oral epithelium model - Santana, Luana Mendonça Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This thesis explores innovative approaches to treat Candida albicans infections in single and mixed-species biofilms when combined also with Streptococcus mutans. The experimental publication 1 evaluated the antimicrobial peptides/proteins (AMPs) Hylin-a1, Temporin-SHa, and KR-12-a5, against fluconazole-resistant and susceptible C. albicans and identified Temporin-SHa as the most promising AMP with significant antifungal and biocompatibility abilities, inhibiting biofilm formation and reducing fungal biomass. Publication 2 assessed the AMPs DR9-RR14, RR14, Histatin 3, and Histatin 5 on mixed biofilms formed on acrylic resin, showing reduced biofilm biomass and extracellular matrix (ECM) vital components disruption. Publication 3 investigated the combined effects of His3 and His5, the most promising AMPs evaluated previously, with antimicrobial photodynamic therapy (aPDT) on mixed biofilms containing three resistant strains of C. albicans and S. mutans, showing enhanced biofilm inhibition and reduced extracellular matrix (ECM) components, also minimizing the virulence of resistant strains and highlighting the synergistic potential of this new approach. Lastly, publication 4 validated the combination of His3 and His5 with aPDT in a 3D oral epithelium model, demonstrating limited infection penetration into deeper layers, reduced hyphal invasion, and compatibility with host tissue. These findings collectively highlight the potential of combining aPDT with AMPs as a targeted approach to overcome microbial resistance and biofilm complexity. Proteomic profiling provided information about the molecular mechanisms by which this combination treatment works, proving its efficacy as a therapy. As a future investigation, the combined treatment validated in this study needs to be extended to in vivo models to evaluate tissue regeneration behavior, particularly after the remission of the lesions.

Esta tese explora abordagens inovadoras para o tratamento de infecções por Candida albicans em biofilmes de espécie única e em associação com Streptococcus mutans. A primeira publicação experimental avaliou os peptídeos/proteínas antimicrobianos (AMPs) Hylin-a1, Temporin-SHa e KR-12-a5 contra cepas de C. albicans resistentes e suscetíveis ao fluconazol, identificando o Temporin-SHa como o AMP mais promissor, com significativa atividade antifúngica e biocompatibilidade, capaz de inibir a formação de biofilmes e reduzir a biomassa fúngica. A segunda publicação analisou os AMPs DR9-RR14, RR14, Histatina 3 (His3) e Histatina 5 (His5) em biofilmes mistos formados sobre resina acrílica, demonstrando redução da biomassa do biofilme e redução de componentes vitais da matriz extracelular (MEC). Na terceira publicação, foram investigados os efeitos combinados de His3 e His5, identificados anteriormente como os AMPs mais promissores, com a terapia fotodinâmica antimicrobiana (aPDT) em biofilmes mistos contendo três cepas resistentes de C. albicans associadas a S. mutans. Os resultados revelaram inibição significativa dos biofilmes, redução de componentes da MEC e diminuição da virulência das cepas resistentes, destacando o potencial sinérgico desta nova abordagem. Por fim, a quarta publicação validou a combinação de His3 e His5 com a aPDT em um modelo tridimensional (3D) de epitélio oral, evidenciando penetração limitada da infecção em camadas mais profundas, redução da invasão hifal e compatibilidade com o tecido hospedeiro. Coletivamente, esses achados ressaltam o potencial da combinação entre aPDT e AMPs como uma estratégia direcionada para superar a resistência microbiana e a complexidade dos biofilmes. A análise proteômica forneceu informações relevantes sobre os mecanismos moleculares pelos quais esse tratamento combinado atua, comprovando sua eficácia terapêutica. Como perspectiva futura, destaca-se a necessidade de expandir a investigação deste tratamento combinado para modelos in vivo, a fim de avaliar o comportamento de regeneração tecidual, especialmente após a remissão das lesões.
Influência da terapia fotodinâmica combinada com peptídeos antimicrobianos sobre biofilme oral e modelo 3D de epitélio oral humano reconstruído
Keywords: Biofilms; Candida albicans; Streptococcus mutans; Biofilmes; Candida albicans; Streptococcus mutans